Media dan Politik - Rafiqa Syahidah Ritonga (Ittishol: Jurnal Komunikasi dan Dakwah, 2023)
The relationship between media and politics is often faced with various problems that influence the dynamics of information, public opinion and the political process itself. The media is often criticized for having political biases that can influence the way news is presented and opinions are conveyed to the public. The media sometimes tends to prioritize entertainment aspects or sensational content rather than providing in-depth and balanced coverage of complex political issues. Media, especially social media, often becomes a forum for spreading false information or hoaxes, which can influence people's understanding of political issues and trigger information uncertainty. There is debate about ethics in reporting, especially regarding privacy, how images or recordings are taken, and how the media reports certain situations. Understanding these issues is important to help increase public media literacy, encourage transparency in reporting, and promote reliable and balanced sources of information to support a healthy political process. Mass media is not only a channel of information, but also plays a role in shaping public opinion and the political process. By understanding the complexity of the relationship between media and politics and the challenges they face, it is important to continue to fight for transparency, integrity and pluralism in political information conveyed to the public. This is an important foundation in supporting a healthy political process and better public participation in political life.